SME MARKETING STRATEGIES IN BOGOR CITY AFTER MUI FATWA ON BOYCOTTING PRO-ISRAEL PRODUCTS - Novianti La Daera (Department Islamic Economics, 2025)
This research aims to understand how MSME actors in the fast food and beverage sector leverage boycott opportunities to increase sales, the strategies employed by MSMEs to expand marketing, and consumer attitudes in obtaining and determining substitute products. Observation, documentation, interviews, and questionnaires are some of the data collection methods employed in this descriptive qualitative approach. The Miles and Huberman data analysis paradigm is then used to process this data. The results of the study showed that MSMEs capitalize on boycott opportunities to boost sales by incorporating pro-Palestinian attributes in their stalls, advertising products on various social media platforms, donating a portion of their income to Palestine, and ceasing the marketing of boycotted products. The strategies employed by MSMEs to expand marketing during the boycott include word of mouth, distributing brochures, advertising products on WhatsApp, promotions, adding product variations, and setting up stands at various events. Consumer attitude in determining the replacement of a boycotted product is by looking for a product that is relatively equivalent in terms of shape, taste, and price and also the ease in obtaining a replacement product. The practical implications of this research are to encourage MSMEs to innovate in sales so that the products they sell are known to the wider public and as a substitute for boycotted fast food products